JURIDICAL REVIEW OF STEP FATHER'S ABILITY AGAINST CHILDREN (CASE STUDY OF DELI SERDANG CHILD PROTECTION INSTITUTE) - Yusfirda Aziza Rangkuti; Nelvitia Purba (Fox Justi : Jurnal Ilmu Hukum, 2022)
This study aims to determine the legal arrangements against child molestation by stepfathers. The method used in this research is Juridical Empirical or called field research, which is to examine the applicable legal provisions and what happens in reality in society. Empirical juridical research is legal research regarding the enforcement or implementation of normative legal provisions in action on certain legal events that occur in society. In this study, the classification of criminal acts of harassment is regulated in several laws and regulations, such as the Criminal Code, Law no. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection and the PKDRT Law.